Self-expandable metal stent placement in a child for treatment of achalasia after failed Heller myotomy - Gugig, Roberto; Muñoz Jurado, Guillermo; Huang, Clifton; Oleas, Roberto; Robles-Medranda, Carlos (Endoscopy International Open, 2018)
Background and study aims Childhood achalasia treatment remains inconclusive. What is next after myotomy failure? Repeated pneumatic-dilation put patients at greater risk of perforation with possible symptom recurrence. We report on a 12-year-old patient with a 1-year history of achalasia whom underwent Heller myotomy with fundoplication and recurred with symptoms 1 week after surgery. Pneumatic dilatation was considered but not done because of the risk of esophageal perforation. The decision was made to place a fully covered self-expanding metallic stent (FC-SEMS) for 3 months, which resolved the stenosis as confirmed by esophagram. The patient has remained asymptomatic since the procedure was performed 2 years ago. FC-SEMS is an alternative for treatment of refractory achalasia in children who do not respond to conventional treatment.